Microstructural, optical properties and thermal stability of MgO/Zr/MgO multilayered selective solar absorber coatings. (January 2015) - Nuru, Z.Y.; Msimanga, M.; Muller, T.F.G.; Arendse, C.J.; Mtshali, C.; Maaza, M.
Highlights: MgO/Zr/MgO selective solar absorber was fabricated using e-beam evaporator. Solar absorptance ∼0.92 and low thermal emittance ∼0.09 was achieved. MgO/Zr/MgO solar absorber was thermally stable in vacuum up to 400 °C for 2 h. At 500 °C, oxidation of the Zr base layer and diffusion towards the surface were seen. Abstract: MgO/Zr/MgO multilayered selective solar absorber coating (MSSAC) was deposited onto Zr coated stainless steel substrates using e-beam evaporation. The MSSAC exhibited a solar absorptance of about 0.92 in the solar spectrum range and low thermal emittance of about 0.09 in the infrared range. Optical constants of the MSSAC were determined from the experimentally measured reflectance spectra. The MgO/Zr/MgO MSSAC was found to be thermally stable up to 400 °C. However at 500 °C, the solar absorptance decreased to 0.893 from 0.918, and the thermal emittance increased to 0.12 from 0.10. The change in the optical properties is attributed to the outward diffusion of Zr towards the surface as well as oxidation of the Zr base layer and a change in the chemical composition of MgO as probed by Heavy Ion Elastic Recoil Data Analysis.